2020
DOI: 10.1080/0284186x.2019.1711164
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk markers of 5-fluorouracil and capecitabine cardiotoxicity in patients with colorectal cancer

Abstract: Background: Fluoropyrimidines are mainstay chemotherapeutics in the treatment of gastrointestinal cancers and are also used to treat breast cancer and head and neck cancers. However, 5-flourouracil (5-FU) and capecitabine may induce cardiotoxicity that mostly presents as acute coronary syndromes. We compared the incidence of cardiotoxicity induced by 5-FU and capecitabine in patients with colorectal cancer and sought to identify risk markers for cardiotoxicity. Methods: We reviewed all consecutive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…EST was planned after at least 10 days of treatment to increase its sensitivity because FP cardiotoxicity is more frequent in prolonged therapies. 16 , 24 , 42 We observed more cases of stress-induced cardiotoxicity than rest cardiotoxicity (26 vs. 6). In 12 cases the toxicity was evident after a workload of < 4.6 Metabolic Equivalents of Task (METs), corresponding to activities as digging, making beds, walking upstairs, washing windows, mowing the lawn, painting a wall, bicycling at 10 km/h.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…EST was planned after at least 10 days of treatment to increase its sensitivity because FP cardiotoxicity is more frequent in prolonged therapies. 16 , 24 , 42 We observed more cases of stress-induced cardiotoxicity than rest cardiotoxicity (26 vs. 6). In 12 cases the toxicity was evident after a workload of < 4.6 Metabolic Equivalents of Task (METs), corresponding to activities as digging, making beds, walking upstairs, washing windows, mowing the lawn, painting a wall, bicycling at 10 km/h.…”
Section: Discussionmentioning
confidence: 71%
“… 5 , 8 , 15 , 19-27 Retrospective studies (based on symptoms reported in the clinical charts) report an incidence of 4.3-7%. 13 , 21 , 24-26 Two prospective studies based on symptoms found 5.5-6.5% of capecitabine cardiotoxicity, 9 , 10 while other prospective studies including ECG found rates of 8.5-35% fluoropyrimidine cardiotoxicity. 8 , 14-16 , 23 , 27 , 28 Some of these studies, however, included in the term “cardiotoxicity” ECG changes of little, if any, clinical significance, as asymptomatic sinus bradycardia or PR and QT changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiotoxicity is an uncommon but important side effect of 5-FU and capecitabine, seen in about 5% of patients, and encompasses a wide spectrum of effects, including electrocardiogram changes to myocardial infarction and cardiogenic shock, which may lead to anything from dose reduction, interruption of planned chemotherapy regimens to, albeit rarely, sudden death [58]. 5-FU re-challenge may be undertaken with vigilant cardiac monitoring and the combined use of calcium channel blockers and nitrates [59].…”
Section: Refinement Of Chemotherapy Regimens Employing Approved Folatesmentioning
confidence: 99%
“…However, the risk of developing trastuzumab cardiotoxicity has been seen to increase in patients who receive concurrent anthracycline therapy [ 90 , 95 , 96 ]. When trastuzumab suppresses ErbB2 signaling, it was reported that it further accelerates the anthracycline’s ability to induce sarcomeric protein breakdown, increasing the chances of cardiac toxicity and heart failure [ 97 ].…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%